Towards a Wearable Device for Monitoring Ecological Environments - Delabrida, Saul Emanuel; D'Angelo, Thiago; Oliveira, Ricardo A. Rabelo; Loureiro, Antonio Alfredo Ferreira (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
Wearable devices have emerging in last years with diverse applications for provide user convenience. Health care, sports, safety are some examples of areas in which wearable devices have been applied. This paper describes an overview about wearable architectures found in the literature and presents a novel wearable for monitoring ecological environments. The wearable is composed of a Head-UP Display (HUD) assembled with Google Cardboard API and sensors connected to a development board. Our wearable device provides several functionalities such as distance measurement to objects and weather conditions monitoring. Camera and green lasers combined with a digital image processing algorithm are used to measure the distance to objects. Our system is evaluated in different development boards.